PEMASARAN TRADISIONAL DAN PEMASARAN KEWIRAUSAHAAN: PENGARUHNYA TERHADAP KINERJA USAHA KECIL ETNIS JAWA DAN MADURA - Ernani Hadiyati; Enlik Kresnaini (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
The role of SMEs in the national economy has involved the government, it is appropriate in the Program of the National Medium Term Development Plan 2004-2009. One small problem is the marketing and generally focused on three things: (1) product market competition, (2) access to market information, and (3) support the institutional business. To overcome the problems of marketing, human resource needs in conducting marketing activities to have a high entrepreneurial spirit. The study population is small businesses: industrial clothing, embroidery, batik, shoes, sandals, handbags, and luggage, furniture, ceramics and printing. The number of samples in this study is set at: 100 respondents including Javanese and Madurese 50% Ethnic 50%. Data analysis techniques used are grouped into two categories, namely descriptive statistics and structural equation model (Structural Equation Modeling). Descriptive statistics were used to analyze data in ways that explain or describe the data have been collected and are not intended to create a generally accepted conclusions or generalizations. The results showed that: Traditional Marketing significantly influence with entrepreneurship. Traditional marketing significant effects on business performance. Entrepreneurship significantly effects on entrepreneurial marketing. Entrepreneurship significant effect on business performance. Marketing Entrepreneurship significant effect on business performance. There are differences between ethnic entrepreneurs and ethnic Javanese Madura, when viewed in terms of entrepreneurship, entrepreneurial marketing and business performance. However, if viewed in terms of traditional marketing, there is no difference between ethnic Madurese and Javanese businessmen.